2021
DOI: 10.1192/bjo.2021.1060
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of anxiety and depressive symptoms among quarantined individuals: cross-sectional study

Abstract: Background The mental health burden of COVID-19 has been examined in different settings. Existing research has relied on the latent variable model in assessing COVID-19-related distress. Network theory provides an alternative framework wherein symptoms are conceptualised as causal, interconnected constituents rather than outcomes of mental disorders. Aims To assess networks of self-reported anxiety and depressive symptoms among quarantined individuals. Method Consenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Although widely studied, probing into the network-wise architectures of pathopsychological connectome of depression and anxiety was still one of the most promising pathway to understand this transdiagnostic factor 4,44 . In the present study, we found the integrative high centrality of external life meaning perception (e.g., "perceiving meaningless life") and internal emotional exhaustion (e.g., "feeling exhaustion") in this symptom-centered network in a preclinical adult population, which merited to characterize early vulnerable symptoms for "atrisk or preclinical" ones 8,[45][46][47][48][49] . Thus, these findings complement previous studies by revealing preclinical or "at-risk" trans-symptoms to the anxiety and depression.…”
Section: Discussionsupporting
confidence: 54%
“…Although widely studied, probing into the network-wise architectures of pathopsychological connectome of depression and anxiety was still one of the most promising pathway to understand this transdiagnostic factor 4,44 . In the present study, we found the integrative high centrality of external life meaning perception (e.g., "perceiving meaningless life") and internal emotional exhaustion (e.g., "feeling exhaustion") in this symptom-centered network in a preclinical adult population, which merited to characterize early vulnerable symptoms for "atrisk or preclinical" ones 8,[45][46][47][48][49] . Thus, these findings complement previous studies by revealing preclinical or "at-risk" trans-symptoms to the anxiety and depression.…”
Section: Discussionsupporting
confidence: 54%
“…Center and bridge symptoms are vital in triggering and maintaining the disorder network, which might serve as potential intervention targets. Increasing studies applied the network approach to assess anxiety and depression among the general population, college students, adolescents, and clinicians during the COVID-19 pandemic, which documented both common and unique depression-anxiety network across different populations ( 13 – 17 ). However, as far as we know, no previous study described anxiety and depression symptoms among nurses via the network model.…”
Section: Introductionmentioning
confidence: 99%
“…Even though network analysis studies have been conducted during the pandemic of COVID-19 ( Abdul Karim et al, 2021 ; Zavlis et al, 2021 ), clinical features of depression and anxiety, as well as experiences of well-being may vary depending on sample characteristics, culture, socioeconomic status or stressors ( Bai et al, 2021 ). This implies that the results of network analysis in a given group are not easily applicable to other groups.…”
Section: Introductionmentioning
confidence: 99%